DAMPAK PERATURAN PEMERINTAH NOMOR 48 TAHUN 2014 TERHADAP MASYARAKAT DAN PENGHULU (Studi di KUA Gondokusuman dan Tegalrejo Yogyakarta) - Arsyad, Faiz Adzkia (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2017)
Based on Government Regulation Number 48 of 2014 about Marriage Registration Fee which contains about the cost of marrieage recording and referring for free or free of charge when done in KUA. If marriage applied outside KUA and outside working hours, it is charged Rp 600.000. The regulation subtitutes Government Regulation Number 47 of 2004 about Non-Tax State Revenue Rate that applied to the Ministry of Religious Affairs. The weakness of Government Regulation No. 47 of 2004 is the number of gratification practices among some headman. This resulted in the issuance of Government Regulation Number 48 of 2014 concerning about the Cost of marriage listing on the basis of the benefit to eliminate the practice of gratuities. Primary sources in this study are the views of the Head Office of Religious Affairs (KUA) Tegalrejo and Gondokusuman Subdistricts and View of bride and groom candidates in Tegalrejo and Gondokusuman Subdistricts. The secondary data are documents relating to the Office of Religious Affairs (KUA) Tegalrejo and Gondokusuman Sub-districts. The approach used is the normative approach. Data were analyzed qualitatively by using deductive and inductive methods. This paper describes the impact of the implementation of Government Regulation Number 48 of 2014 about the Cost of Marriage Listing in KUA Tegalrejo and Gondokusuman.[Berdasarkan Peraturan Pemerintah Nomor 48 tahun 2014 tentang Biaya Pencatatan Nikah yang berisi tentang biaya pencatatan nikah dan rujuk gratis atau tidak dipungut biaya sama sekali apabila dilakukan di dalam KUA. Jika melaksanakan nikah di luar KUA dan di luar jam kerja, maka dipungut biaya sebesar Rp 600.000. Peraturan tersebut menggantikan Peraturan Pemerintah Nomor 47 tahun 2004 tentang Tarif Penerimaan Negara Bukan Pajak yang Berlaku pada Departemen Agama. Kelemahan PP Nomor 47 tahun 2004 adalah banyaknya praktek gratifikasi di kalangan oknum penghulu. Hal ini menyebabkan lahirnya Peraturan Pemerintah Nomor 48 tahun 2014 tentang Biaya Pencatatan Nikah atas dasar kemaslahatan untuk menghilangkan praktek gratifikasi. Sumber primer dalam penelitian ini adalah Pandangan Kepala Kantor Urusan Agama (KUA) Kecamatan Tegalrejo dan Gondokusuman serta Pandangan Calon Manten di Kecamatan Tegalrejo dan Gondokusuman. Data sekundernya adalah dokumen yang berhubungan dengan Kantor Urusan Agama (KUA) Kecamatan Tegalrejo dan Gondokusuman. Pendekatan yang digunakan adalah pendekatan normatif. Data dianalisis secara kualitatif dengan menggunakan metode deduktif dan induktif. Tulisan ini menjelaskan tentang dampak implementasi Peraturan Pemerintah Nomor 48 tahun 2014 tentang Biaya Pencatatan Nikah di KUA Tegalrejo dan Gondokusuman.]